Study of Energetic Materials of Double Base Propellant for Small Caliber Ammunition - Khevinadya Ramadhani Runtu; Leni Tria Melati; Igara Triregina; Gathut Imam Gunadi; Prita Nur Wahyu; Ice Fahmi; Nanang Hary Soebakgijo; Mas Ayu Elita Hafizah; Yayat Ruyat (Jurnal Inotera, 2023)
Double Base Propellants (DBP) has been frequently utilized in the fields of rocket propellant and gun propellant. DBP has various advantages over conventional propellants, including easy formulation, high energy, and smokelessness. The research conducted in literature studies was applied by referring to the various energetic materials for DBP. The composition of a DBP consists of energetic raw material of Nitrocellulose (NC) and Nitroglycerin (NG). According to data analysis, NC can be manufactured from the raw material Nata de Coco, which has a nitrogen content of more than 12,5% in NC, which is in line with the levels of conventional military and propellant raw materials. Meanwhile, SMX (1,4-dinitrate-2,3-dinitro-2,3bis (nitratomethylene) butane) or GAP (Glycidyl Azide Polymer) on double-base propellants is suggested as potential alternative energy sources that can be utilized to substitute NG. The choice of new energetic material is influenced by the fact that Nata de Coco is abundant in Indonesia, while SMX and GAP in terms of manufacturing and handling are safety. The several parameters to characterize double-base propellants include thermal analysis, microstructure, surface area, burning rate value, and gaseous product. The results of thermal properties by DSC analysis on a DBP based on NC+NG+TiO2-trifluoroacrylate showed a change in exothermic decomposition at a temperature of 199.2oC. Meanwhile, TGA analysis of a DBP based on NC+NG+GAP showed mass decomposition at temperature 199,3oC. Furthermore, it was found that thermoplastic elastomers GAP have a significant effect on increasing the low-temperature mechanical properties of double-base propellants. As a result, the literature studies approach, which includes consideration of alternative energetic raw materials and characterization for double-base propellants, is the recommendation for obtaining superior performance double-base propellants with energetic materials.